1992
DOI: 10.1044/jshr.3506.1406
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Fundamental, Resolved Harmonics, and Unresolved Harmonics in Tone-Phoneme Identification

Abstract: Researchers describe Mandarin Chinese tone phonemes by their fundamental frequency (Fo) contours. However, tone phonemes are also comprised of higher harmonics that also may cue tone phonemes. We measured identification thresholds of acoustically filtered tone phonemes and found that higher harmonics, including resolved harmonics above the Fo and unresolved harmonics, cued tone phonemes. Resolved harmonics cued tone phonemes at lower intensity levels suggesting they are more practical tone-phoneme cues in ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Most formant transitions have durations of less than 50 msec, and very brief FM sweeps of 5-20 msec with rates exceeding 30 octaves per second have been used in several studies to examine processing of formant transitions (A. M. Liberman et al, 1956;Luo et al, 2007;Miller & Liberman, 1979). Rapid FM sweeps have also been employed in the study of tonal languages (e.g., Chinese or Thai), where pitch contour variations affect lexical distinction (Howie, 1976;Luo et al, 2007;Stagray, Downs, & Sommers, 1992). The study of FM transitions in speech has also had practical applicability for language processing by children afflicted with language-based learning impairment (LLI).…”
Section: Resultsmentioning
confidence: 99%
“…Most formant transitions have durations of less than 50 msec, and very brief FM sweeps of 5-20 msec with rates exceeding 30 octaves per second have been used in several studies to examine processing of formant transitions (A. M. Liberman et al, 1956;Luo et al, 2007;Miller & Liberman, 1979). Rapid FM sweeps have also been employed in the study of tonal languages (e.g., Chinese or Thai), where pitch contour variations affect lexical distinction (Howie, 1976;Luo et al, 2007;Stagray, Downs, & Sommers, 1992). The study of FM transitions in speech has also had practical applicability for language processing by children afflicted with language-based learning impairment (LLI).…”
Section: Resultsmentioning
confidence: 99%
“…Poeppel, 2003). Importantly, supra-segmental FM forms the basis for the lexical distinctions in tone languages, such as Mandarin Chinese or Thai, both of which use highly constrained and parameterized pitch contour variations to make lexical distinctions (Howie, 1976;Stagray et al, 1992). For example, the segmental sequence, [ma], has four distinct meanings in Mandarin Chinese when spoken with different supra-segmental (or 'global') pitch contours.…”
Section: Introductionmentioning
confidence: 99%
“…On average, greater than 80% tone recognition levels were achieved for almost all low frequency cuts and S/N ratios, except for condition LC18 and S/N -10. A 66.8% recognition level was reached in LC18 and S/N -10, indicating that harmonic cues might play as important a role in such adverse listening conditions for tone perception, as they do in quiet [6] . In brief, a tone recognition score above 80% was maintained regardless of the influence of low frequency cuts and noise for normal-hearing listeners, except for the very adverse listening condition LC18 and S/N -10.…”
Section: Impact Of Low Frequency Cut and Noise On Tone Recognitionmentioning
confidence: 94%
“…Stagray et al [6] further explored the role of harmonics by measuring the identification thresholds of acoustically filtered Mandarin phonemes and found that higher harmonics still cued tone phonemes. These findings were consistent with predictions based on our knowledge of pitch perception for nonspeech, complex tones.…”
mentioning
confidence: 99%